Hubungan pola bermain gadget dengan kemampuan kognitif dan berpikir kreatif pada anak usia prasekolah (5-6 tahun) - Hasriani, St; Asnuddin, Asnuddin; Bebang, Asnal; Akib, Resky Devi; Nurdin, Nurhidayah (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Cognitive development is the basis for a child's ability to think. The cognitive structure in a child is very fast. Creative thinking is a series of processes, including understanding the problem, making guesses and hypotheses about the problem, finding answers, proposing evidence, and finally reporting the results. Purpose: To determine the relationship between gadget playing patterns and cognitive and creative thinking abilities in preschool children (5-6 years). Method: The type of research is a cross-sectional study method conducted from October 4 to October 20, 2024 at RA Dharmawanita, Ministry of Religion and TK Al Barokah, as many as 30 children as samples using purposive sampling technique. Results: The relationship between gadget playing patterns and cognitive and creative thinking abilities in preschool children (5-6 years) obtained statistical test results on the cognitive ability variable with a p value = 1,000>0.05 and on the creative thinking variable a p value = 0.013 <0.05 was obtained. Conclusion: There is no relationship between gadget playing patterns and cognitive abilities in preschool children (5-6 years). In addition, based on the results of the study, it was stated that there is a relationship between gadget playing patterns and creative thinking. Keywords: Cognitive Ability; Creative Thinking; Gadgets. Pendahuluan: Perkembangan kognitif merupakan dasar bagi kemampuan anak untuk berpikir. Struktur kognitif yang ada pada seorang anak sangat cepat. Berpikir kreatif merupakan serangkaian proses, termasuk memahami masalah, membuat tebakan dan hipotesis tentang masalah, mencari jawaban, mengusulkan bukti, dan akhirnya melaporkan hasilnya. Tujuan: Untuk mengetahui hubungan pola bermain gadget dengan kemampuan kognitif dan berpikir kreatif pada anak usia prasekolah (5-6 Tahun). Metode: Jenis penelitian metode cross sectional Study yang dilakukan 4 oktober-20 Oktober 2024 di RA Dharmawanita kementerian agama dan TK Al Barokah sebanyak 30 anak sebagai sampel dengan teknik purposive sampling. Hasil: Hubungan pola bermain gadget dengan kemampuan kognitif dan berpikir kreatif pada anak usia prasekolah (5-6 Tahun) memperoleh hasil uji statistik pada variabel kemampuan kognitif dengan nilai p = 1.000>0.05 dan pada variabel berpikir kreatif diperoleh nilai p = 0,013 < 0,05. Simpulan: Tidak ada hubungan pola bermain gadget dengan kemampuan kognitif pada anak usia prasekolah (5-6 tahun). Selain itu, berdasarkan hasil penelitian dinyatakan bahwa ada hubungan pola bermain gadget dengan berfikir kreatif. Kata Kunci: Berpikir Kreatif; Gadget; Kemampuan Kognitif.